2012
DOI: 10.1159/000337399
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Family Structure on Dental Caries Experience of Preschool Children in Sri Lanka

Abstract: Background: The prevalence of dental caries in preschool children has not been declining in the recent past. A growing body of research suggests that social and behavioural factors may play a considerable role in the aetiology of dental caries. Aims: The objective of this study was to determine the relationship between the family structure and dental caries experience in preschool children. Methods: A descriptive cross-sectional study was carried out in children aged 3–5 years in Wattala Divisional Secretariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 17 publications
5
25
2
Order By: Relevance
“…In the present study, place of residence, mother's schooling and household income were used as socioeconomic indicators and categorised based on the characteristics of the population studied. Other studies have used variables such as family size and the number of siblings or different ways of categorising variables such as mother's schooling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, place of residence, mother's schooling and household income were used as socioeconomic indicators and categorised based on the characteristics of the population studied. Other studies have used variables such as family size and the number of siblings or different ways of categorising variables such as mother's schooling.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence rate of ECC is influenced by socio‐demographic factors and oral hygiene practices. Studies have demonstrated that a low level of education on the part of parents/guardians, insufficient knowledge on oral health, a low income and unsatisfactory oral hygiene exert a considerable influence on dental caries experience.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that household overcrowding had an inverse relationship with healthy habits of nutrition and hygiene, oral health-related quality of life, and were predictors of traumatic dental injuries in children and adolescents [2,37-39]. Thus, overcrowding may have both direct and indirect effects on the general and oral health of the members of families, and poorer schoolchildren living in homes with fewer individuals was a protective factor for curative dental needs.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies in this area are small, and the subgroups of birth order vary. Although risk of dental caries in later-born children compared to first-born children has been found to be higher [9,10], conflicting results have also been reported [11,12].…”
Section: Introductionmentioning
confidence: 97%